Project Masiluleke : texting and testing to fight HIV/AIDS in South Africa - Canales, Rodrigo (London : SAGE Publications Ltd, 2017)
When Krista Dong and Zinhle Thabethe came to the 2006 PopTech conference in Camden, Maine, they hoped to expand their fight against HIV/AIDS, one of South Africas greatest problems. They were the founders of iTEACH, an HIV/AIDS and TB prevention and treatment program in KwaZulu-Natal, South Africa. Impressed by their story, conference organizers and Robert Fabricant of frog design came together with iTEACH to address these real-world challenges through the conferences vision accelerating social innovation through technology.
Originally published: Conales, R. (2011). Project Masiluleke: Texting and testing to fight HIV/AIDS in South Africa. 10-026. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol10.cases.som.yale.edu/project-m.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Dong, Krista; Thabethe, Zinhle; iTEACH; AIDS (Disease) -- South Africa -- Prevention -- Case studies; HIV infections -- South Africa -- Prevention -- Case studies; Technological innovations -- South Africa -- Case studies